1994
DOI: 10.1093/schbul/20.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selenium and Other Trace Elements in the Geography of Schizophrenia

Abstract: Medical geology is the application of trace element geography to epidemiology. This approach is used to compare the geographic distribution of selenium and other trace elements in soil and food with that of high schizophrenia rates in the United States and other countries. Since the comparison is most statistically significant for low selenium, the selenium theory of schizophrenia is evaluated by the principles of environmental epidemiology. Although this examination finds the theory deficient, research questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 65 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…Apart from its role in binding selenium, it has been localized to the golgi apparatus, is localized to the growing tips of neurons, and has been associated with ovarian cancer [Huang et al, 2006]. An epidemiological study has shown that regions of the United States with selenium deficiency in the soil are associated with higher frequencies of schizophrenia [Brown, 1994], and other studies have demonstrated that selenium deficiency can directly regulate glutamate-induced oxidative stress in the brain [Ramaekers et al, 1994;Savaskan et al, 2003]. Although such disparate findings still preclude us from advancing a unifying theory on the role of SELENBP1 in psychosis, they do generate interesting empirical questions for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role in binding selenium, it has been localized to the golgi apparatus, is localized to the growing tips of neurons, and has been associated with ovarian cancer [Huang et al, 2006]. An epidemiological study has shown that regions of the United States with selenium deficiency in the soil are associated with higher frequencies of schizophrenia [Brown, 1994], and other studies have demonstrated that selenium deficiency can directly regulate glutamate-induced oxidative stress in the brain [Ramaekers et al, 1994;Savaskan et al, 2003]. Although such disparate findings still preclude us from advancing a unifying theory on the role of SELENBP1 in psychosis, they do generate interesting empirical questions for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the up‐regulation of SEPX1 may play a role in the pathophysiology of schizophrenia. Geographical analysis showed that low selenium in soil and food might be associated with schizophrenia [Brown, 1994]. At deficiency selenium is preferentially retained in the brain compared with other organs, and several studies have shown that selenium deficiency is associated with mood [Benton, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies of heavy the time of conception, and Templer et al (1978), who reported ''a rather consistent trend of schizometals such as magnesium ( Yassa et al, 1979), zinc (Andrews, 1990), and selenium (Foster, 1988; phrenics being born in cold months and conceived in warm months ''. McNeil et al (1975), studying Berry, 1994;Brown, 1994) have been reported to cause schizophrenia-like syndromes. Similarly, a sample of 13 440 individuals with schizophrenia in Sweden, was unable to corroborate an associaexposure to industrial chemicals, such as toluene, is also known occasionally to cause schizophreniation between summer temperatures at the time of conception and winter births of individuals with like syndromes (Goldbloom and Chouinard, 1985).…”
Section: Seasonal Variation In External Toxins 89 Temperature and Wmentioning
confidence: 99%